Experiences of kidney transplantation for recipients in regional, rural, and remote Queensland – exploring the trials and tribulations - Tara K. Watters; Beverley D. Glass; Nicole J. Scholes-Robertson; Andrew J. Mallett (BMC Nephrology)
Abstract Background People with kidney failure, unable to access kidney transplantation are disadvantaged in terms of their quality of life and overall survival. Despite this, regional, rural, and remote populations worldwide remain less likely to receive a kidney transplant and often experience unique difficulties throughout their transplant journey. This study aimed to explore the experiences of these kidney transplant recipients, including around current transplant processes to understand barriers to access for regional, rural, and remote populations. Methods Focus group discussions were conducted either in-person or online with kidney transplant recipients from regional, rural, and remote areas of northern Queensland. Transcripts were analysed thematically with emerging themes mapped against constructs of Levesque’s patient-centred healthcare access framework. Results Focus group participants (n = 30) included both deceased (90%) and living (10%) donor transplant recipients, with almost a third (30%) of which resided in rural or remote areas. Six themes were identified relating to access to kidney transplantation: facing hurdles to transplant assessment, insufficient communication and education, permeating psychosocial hazards, repercussions of distance, overwhelming financial strain, and troubling long-term adversities. Conclusions Kidney transplant recipients from regional, rural, and remote areas of northern Queensland described significant barriers throughout their transplantation journey. These relate primary to their geographical distance from specialty kidney transplant services and the subsequent logistic, financial, and psychosocial challenges that arise. Clinical trial registration This study was not a clinical trial.